Application of emerging technologies in ischemic stroke: from clinical study to basic research - Chen, Qiuyan; Zhang, Shuxia; Liu, Wenxiu; Sun, Xiao; Luo, Yun; Sun, Xiaobo (Frontiers in Neurology, 2024)
Stroke is a primary cause of noncommunicable disease-related death and disability worldwide. The most common form, ischemic stroke, is increasing in incidence resulting in a significant burden on patients and society. Urgent action is thus needed to address preventable risk factors and improve treatment methods. This review examines emerging technologies used in the management of ischemic stroke, including neuroimaging, regenerative medicine, biology, and nanomedicine, highlighting their benefits, clinical applications, and limitations. Additionally, we suggest strategies for technological development for the prevention, diagnosis, and treatment of ischemic stroke.